Kinetic and Equilibrium Study of Synthetic Dye Adsorption Using Alkali-Activated Scallop Shells as Sustainable Adsorbents - Muhammad Naoval Haris; Aditya Dimas Wahyu Sasongko; Farchan Mushaf Al Ramadhani (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Scallop shells are abundant in Indonesia, particularly along the northern coast of Java Island in Pekalongan Regency. These shells serve as natural adsorbents for removing synthetic textile dyes from aqueous solutions due to their high mineral content, especially calcium carbonate. Adsorption experiments were conducted to evaluate the potential of scallop shells as adsorbents for removing vat dye solutions. Adsorption kinetics were analyzed using pseudo-first-order and pseudo-second-order models in both linear and non-linear forms. The results showed that the non-linear pseudo-first-order model best described the adsorption process, with a qe value of 0.98982 mg/g. Equilibrium studies using Langmuir, Freundlich, and Jovanovic isotherm models indicated that the linear Freundlich model provided the best fit, with an R² of 0.99969, suggesting a heterogeneous adsorption process. These findings confirm that scallop shells are effective and eco-friendly adsorbents for textile dye removal and hold promise for sustainable water treatment. Further studies are suggested under real industrial conditions.